A review of reactive media within permeable reactive barriers for the removal of heavy metal(loid)s in groundwater: Current status and future prospects. (15th October 2021) - Song, Jiangmin; Huang, Guanxing; Han, Dongya; Hou, Qinxuan; Gan, Lin; Zhang, Meng
Abstract: Groundwater contamination with heavy metal (loid)s occurs worldwide. Permeable reactive barriers (PRBs) have been widely accepted as an alternative to traditional ex-situ removal technologies for sustainable in-situ remediation of heavy metal (loid) contaminated groundwater. Reactive media play a key role in efficiently removing target metal (loid) ions with PRBs. The past few decades have seen the rapid development of reactive media within PRBs for the removal of heavy metal (loid)s in groundwater. Recently, more complicated and multifunctional are the up-to-date characteristics of reactive media within PRBs through modifications toward traditional material. This review summarizes recent findings regarding reactive media within PRBs for the removal of heavy metal (loid)s in groundwater. Reactive media are classified into three classes, namely emerging single material, mixed materials, and core-shell materials. The characteristics of metal (loid)s and representative applied-materials for particular metal (loid) remediation with PRBs are presented. The primary mechanisms and factors influencing the reaction of reactive media with heavy metal (loid)s in groundwater are also summarized, and, the regeneration of used materials and the shortcomings of current reactive media investigated in laboratory-to-field application are highlighted. Finally, developmental directions and exploration highlights for PRB material applied to remove heavy metal (loid)s from groundwater in the future are highlighted. This review provides up-to-date insights into the removal of heavy metal (loid)s using reactive media within PRB and collates references for future research and field-scale applications. Graphical abstract: Image 1 Highlights: The current reactive materials investigated are collated and classified based on fabrication types. The widely applied materials and critical treatment mechanisms toward specific metal(loid)s are summarized. The gaps between laboratory study and practical application on current materials within PRBs are pointed out.